2011
DOI: 10.1074/jbc.m111.221754
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of α7 Nicotinic Receptor Is Governed by Coupling Strength Relative to Gate Tightness

Abstract: Binding of a neurotransmitter to its membrane receptor opens an integral ion conducting pore. However, prolonged exposure to the neurotransmitter drives the receptor to a refractory state termed desensitization, which plays an important role in shaping synaptic transmission. Despite intensive research in the past, the structural mechanism of desensitization is still elusive. Using mutagenesis and voltage clamp in an oocyte expression system, we provide several lines of evidence supporting a novel hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Previous studies (Unwin, 2005;Zhang et al, 2011) have shown that the A272 residue in the M2-M3 linker is a key regulator of channel coupling and gating (Fig. 1B).…”
Section: Coupling Between M1 and The M2-m3 Linker Affects The Singlecmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous studies (Unwin, 2005;Zhang et al, 2011) have shown that the A272 residue in the M2-M3 linker is a key regulator of channel coupling and gating (Fig. 1B).…”
Section: Coupling Between M1 and The M2-m3 Linker Affects The Singlecmentioning
confidence: 93%
“…In particular, the Cys-loop in this region has been demonstrated to play a role in the coupling between the binding domain and the gating machinery in Cys-loop receptors (Bouzat et al, 2008(Bouzat et al, , 2004Rayes et al, 2009;Sala et al, 2005). In our previous studies (Zhang et al, 2011), certain residues in the Cysloop of the a7 receptor were substituted with the corresponding residues in the 5-HT 3A receptor sequence, resulting in the mutant V132I/R133Y/W134N. Given that the 5-HT 3A receptor desensitizes more slowly than the a7 receptor, we expected that the resulting chimera would exhibit kinetics between those of the two parent receptors.…”
Section: Mutation Of the Cys-loop In The Coupling Region Impaired Thementioning
confidence: 97%
See 2 more Smart Citations
“…The diverging occupancy-activation relationship for the α7-5HT 3 A chimera demonstrates that the transmembrane domain or the interface between the transmembrane and extracellular domains that differs between α7 and α7-5HT 3 A (13), or an interplay with the ligand binding domain contribute to this relationship. It remains to be elucidated whether desensitization, which may contribute to α7 open-channel lifetime through a not yet fully known structural mechanism (10,(34)(35)(36), affects this relationship.…”
Section: Discussionmentioning
confidence: 99%